STUDI KOMPARATIF PREDIKSI PROFIL ADMET OBAT SINTETIS DENGAN SENYAWA AKTIF TANAMAN HERBAL ANTIMALARIA MELALUI PENDEKATAN IN SILICO - Rima Rasida; Pinanga, Yangie Dwi Marga; Anjar Hermadi Saputro; Damayanti, Sophi (School of Pharmacy Institut Teknologi Bandung, 2024)
Resistance to antimalarial drugs has become a global challenge in achieving the target of malaria eradication. To address this issue, effective and safe alternative treatments are urgently needed. This study compares the ADMET profiles (absorption, distribution, metabolism, excretion, and toxicity) of synthetic antimalarial drugs with active compounds derived from herbal sources using an in-silico approach. The analyzed herbal compounds, including piperine, kaempferol, berberine, quassin, and limonin, demonstrated high intestinal absorption (>30%), good water solubility, and sufficient skin permeability. In the distribution analysis, kaempferol exhibited high volume distribution due to its lipophilic interactions with body tissues, although most compounds were unable to penetrate the blood-brain barrier. The herbal compounds piperine and kaempferol inhibited metabolic enzymes CYP2C19 and CYP1A2, whereas synthetic drugs tended to act as substrates. Regarding excretion, piperine served as a renal OCT2 substrate, while pyrimethamine exhibited low clearance. Toxicity assessments revealed that herbal compounds generally exhibited better toxicity profiles compared to synthetic drugs, with limonin showing the lowest acute and chronic toxicity. These findings suggest that herbal active compounds hold significant potential for development as alternative antimalarial agents, particularly in addressing drug resistance. This study highlights the importance of further developing herbal-based drugs through in silico approaches to enhance the efficacy and safety of malaria therapy. Keyword : malaria drug resistance, active herbal compounds, ADMET, In silico